2001
DOI: 10.1128/aem.67.12.5824-5829.2001
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Biodegradation of Methyl tert -Butyl Ether by Aquifer Bacteria from Leaking Underground Storage Tank Sites

Abstract: The potential for aerobic methyl tert-butyl ether (MTBE) degradation was investigated with microcosms containing aquifer sediment and groundwater from four MTBE-contaminated sites characterized by oxygenlimited in situ conditions. MTBE depletion was observed for sediments from two sites (e.g., 4.5 mg/liter degraded in 15 days after a 4-day lag period), whereas no consumption of MTBE was observed for sediments from the other sites after 75 days. For sediments in which MTBE was consumed, 43 to 54% of added [U-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 26 publications
2
50
0
Order By: Relevance
“…(ϳ99% similarity to PM1, based on the 16S rRNA gene) (38,67,82). PM1-like bacteria occur naturally in a number of MTBE-contaminated aquifers in the United States (46,47,82), Mexico (21), and Europe (55,61), and their presence has been correlated with MTBE degradation activity in numerous sites (47,67,82), using real-time PCR analysis (37). These results suggest that PM1-like organisms may play a major role in MTBE biodegradation under aerobic conditions in contaminated aquifers.…”
mentioning
confidence: 99%
“…(ϳ99% similarity to PM1, based on the 16S rRNA gene) (38,67,82). PM1-like bacteria occur naturally in a number of MTBE-contaminated aquifers in the United States (46,47,82), Mexico (21), and Europe (55,61), and their presence has been correlated with MTBE degradation activity in numerous sites (47,67,82), using real-time PCR analysis (37). These results suggest that PM1-like organisms may play a major role in MTBE biodegradation under aerobic conditions in contaminated aquifers.…”
mentioning
confidence: 99%
“…Different authors recently reported the biodegradation of MTBE by microcosms from different origins Fortin et al, 2001;Kane et al, 2001;Landmeyer et al, 2001;Park and Cowan, 1997;Salanitro et al, 1994). Moreover, the cometabolic degradation of MTBE was shown to be an important mechanism for MTBE biodegradation using microrganisms able to grow on gaseous alkanes (Hardison et al, 1997;Steffan et al, 1997;Hyman and O'Reilly, 1999;Liu et al, 2001;Hyman et al, 2000), pentane (Garnier et al, 1999), camphor (Steffan et al, 1997), ethanol (Piveteau et al, 2000) or cyclohexane (Corcho et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a stable aerobic mixed culture that degraded MTBE via TBA was obtained (31). MTBE biodegradation by microcosms having different origins was reported later (5,24,45 MTBE cometabolism was demonstrated by using propanegrown bacteria (35), an n-butane-grown fungus (17), camphorgrown Pseudomonas putida CAM (36), pentane-grown Pseudomonas aeruginosa (14), ETBE-grown Rhodococcus ruber IFP 2007 (20), and a cyclohexane-grown mixed culture (9). Steffan et al (36) proposed a pathway for MTBE biodegradation in which MTBE was sequentially degraded to tert-butyl formate (TBF), tert-butyl alcohol, and 2-hydroxy isobutyrate (HIBA).…”
mentioning
confidence: 99%